Preparation method of a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst

By constructing a self-supported layered porous NiZnM@NiZn-Ni heterostructure catalyst on the surface of foam nickel, the problem of overpotential increase of nickel-based electrocatalysts during alkaline electrolysis of aquatic hydrogen production is solved, and high-efficiency catalytic performance and low cost are achieved The electrocatalytic decomposition effect is suitable for large-scale production.

CN115433962BActive Publication Date: 2025-01-10UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211270895.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-18
Publication Date
2025-01-10
Estimated Expiration
2042-10-18

AI Technical Summary

Technical Problem

The existing nickel-based electrocatalysts have large hydrogen evolution and oxygen evolution overpotentials in the process of alkaline electrolysis of aquatic hydrogen. Long-term electrolysis leads to increased overpotential and activity attenuation, which increases energy consumption and production costs.

Method used

Electrodeposition, heat treatment and corrosion technology are used to construct a self-supported layered porous NiZnM@NiZn-Ni heterostructure catalyst on the surface of foam nickel. By adjusting the proportion of Ni, Zn and M components, a bifunctional catalyst with excellent catalytic activity is formed.

Benefits of technology

It realizes efficient catalytic performance in electrocatalytic decomposition of water, reduces energy consumption and production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115433962B_ABST
    Figure CN115433962B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a self-supporting layered porous nickel-based alloy heterostructure catalyst, and successfully prepares a nickel-based multi-interface heterostructure catalyst with a layered porous structure by the "electrodeposition-heat treatment-corrosion" technology. The self-supporting porous structure of the catalyst greatly increases the electrochemical active area, increases the solid-liquid contact area, exposes more active sites, and greatly improves the catalytic activity of water electrolysis; the interface structure has promoted electronic interaction and improved mass transfer efficiency; the catalyst, as a working electrode, exhibits excellent catalytic activity for hydrogen evolution, oxygen evolution and total water decomposition in alkaline electrolyte. At the same time, the catalyst is low in cost, the preparation method is simple, safe and easy, environmentally friendly, and has excellent catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrocatalytic materials, and in particular to a method for preparing a self-supporting layered porous nickel-based alloy heterostructure catalyst. Background Art

[0002] In recent years, global energy is developing towards carbon-free, low-carbon and green and pollution-free. Hydrogen energy, as a zero-carbon emission energy, has the advantages of cleanliness, environmental friendliness and high energy density. As a mature and simple water cycle hydrogen production technology, water electrolysis in alkaline aqueous solution has the advantages of environmental friendliness, high safety and high hydrogen purity. It can use the surplus electricity of renewable resources such as solar energy and wind energy to drive water to convert into hydrogen energy. It is considered to be the core technology of the future green hydrogen production industry. Industrial alkaline water electrolysis mainly uses nickel-based electrocatalysts, which have good conductivity, high corrosion resistance in alkaline solution and low price, but its hydrogen and oxygen evolution overpotential is still large, and it is easy to dissolve during the long electrolysis process, resulting in increased overpotential and activity decay, resulting in increased energy consumption and production costs. Therefore, the use of a simple method to develop a more efficient nickel-based bifunctional water electrolysis hydrogen production catalyst is of great practical significance for promoting the widespread application of water electrolysis hydrogen production. Summary of the invention

[0003] In view of the above problems, the present invention provides a method for preparing a self-supporting layered porous nickel-based alloy heterostructure catalyst. The preparation method is simple, the structure and composition of the prepared catalyst are controllable and adjustable, the yield is high, the cost is low, there is no target material loss, and as a bifunctional catalyst, it has excellent performance in electrocatalytic water decomposition and is suitable for large-scale production.

[0004] The present invention provides a method for preparing a self-supporting layered porous nickel-based alloy heterostructure catalyst, which adopts the techniques of electrodeposition, heat treatment and corrosion to prepare a layered porous NiZnM@NiZn-Ni heterostructure catalyst in situ constructed on the surface of nickel foam, wherein M is Fe or Co, the surface layer is NiZnM, and the base layer is a two-stage porous NiZn-Ni constructed on the surface of nickel foam, and specifically comprises the following steps:

[0005] (1) immersing the nickel foam in a hydrochloric acid solution for ultrasonic cleaning;

[0006] (2) A mixed solution consisting of NiSO4, ZnSO4, M sulfate and Na3C6H5O7 complexing agent is used as the electroplating solution, and the pH of the electroplating solution is adjusted by H2SO4 solution. In a three-electrode system, a high-zinc alloy coating is electrodeposited on the surface of nickel foam by a constant potential method;

[0007] (3) annealing the sample obtained in the above step (2) under argon or nitrogen protection;

[0008] (4) The sample obtained in the above step (3) is corroded in ammonia, NaOH or KOH solution to obtain a self-supporting hierarchical porous NiZnM@NiZn-Ni heterostructure catalyst.

[0009] As a preferred technical solution, in step (1), the nickel foam is firstly ultrasonicated in a 1-8 mol / L hydrochloric acid solution for 5-40 min, then washed with deionized water and anhydrous ethanol and dried.

[0010] As a preferred technical solution, in the mixed solution of step (2), the concentration of NiSO4 is 0.002-0.02 mol / L, the concentration of ZnSO4 is 0.12-0.4 mol / L, the sulfate of M is FeSO4 or CoSO4, and its concentration is 0.02-0.2 mol / L, the concentration of Na3C6H5O7 is 0.3-0.6 mol / L, the mass fraction of H2SO4 solution is 5-40%, and the pH value is 3.5-6.0.

[0011] As a preferred technical solution, in step (2), nickel foam is used as the working electrode, Pt sheet is used as the counter electrode, saturated calomel electrode is used as the reference electrode, the voltage range used is -1.6 to -1.9 V, and the electrodeposition time is 1 to 3 hours.

[0012] As a preferred technical solution, in step (3), the annealing heat treatment temperature is 400-460° C., the heating rate is 2-10° C. / min, and the annealing time is 3-12 h.

[0013] As a preferred technical solution, the concentration of ammonia water, NaOH or KOH solution in step (4) is 0.5-5 mol / L, the preferred corrosion temperature is 25-45°C, and the preferred corrosion time is 10-50h, to obtain the self-supporting layered porous nickel-based alloy heterostructure catalyst.

[0014] As a preferred technical solution, the preparation method of the self-supporting layered porous nickel-based alloy heterostructure catalyst is characterized by: (1) the atomic percentage of Ni in the high zinc content alloy coating obtained after electrodeposition is 2-20%, the atomic percentage of M is 2-20%, and the atomic percentage of Zn is 60-96%; (2) the atomic percentage of Ni in the self-supporting layered porous nickel-based alloy heterostructure catalyst obtained after corrosion is 20-70%, the atomic percentage of Zn is 15-40%, and the atomic percentage of M is 15-40%.

[0015] As a preferred technical solution, the preparation method of the self-supporting layered porous nickel-based alloy heterostructure catalyst is characterized in that: the self-supporting layered porous NiZnM@NiZn-Ni heterostructure catalyst has a surface layer of a two-stage porous network NiZnM alloy, a primary pore wall and a pore size of 100 to 600 nm, a secondary pore wall and a pore size of 3 to 50 nm, and an alloy layer thickness of 2 to 10 μm; the base layer is a two-stage porous NiZn-Ni constructed on the surface of the nickel foam, a primary pore wall and a pore size of 100 to 900 nm, a secondary pore wall and a pore size of 3 to 100 nm, and an alloy layer thickness of 5 to 20 μm.

[0016] As a preferred technical solution, the self-supporting layered porous nickel-based alloy heterostructure catalyst exhibits excellent catalytic activity and structural stability in hydrogen evolution, oxygen evolution and overall water decomposition.

[0017] Compared with the prior art, the preparation method of a self-supporting layered porous nickel-based alloy heterostructure catalyst in the present invention has the following advantages:

[0018] (1) This method combines electrodeposition, heat treatment, and corrosion technology. By controlling the content of electrodeposited Ni, Zn, and M and the corrosion conditions of the alloy sheet, the ratio of Ni, Zn, and M components in the porous composite material can be continuously adjusted, thereby achieving a continuous adjustment of the composition of the product and micro-regulating the performance of the material;

[0019] (2) Since the material is a composite material and the Ni, Zn and M components are precisely adjustable, the active sites of the material can be improved, the active site density of the material can be increased, and the catalytic performance of the catalyst can be effectively improved;

[0020] (3) Compared with materials with other morphologies, the material prepared by this method has a three-dimensional continuous porous self-supporting structure to avoid the shedding of active substances and the use of polymer binders, thereby improving the catalytic activity of the material. In addition, its continuous structure forms a huge network for electronic and ion conduction, which is conducive to obtaining high conductivity and performance stability. In addition, the preparation of self-supporting hierarchical porous NiZnM@NiZn-Ni heterostructure catalysts by this method is simple, easy to operate, reproducible, and has high yield, and there is no loss of target materials during the preparation process.

[0021] In summary, the technical solution of the present invention is simple to operate, has controllable and adjustable structural components, high yield, no target material loss, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Scanning electron microscope image and X-ray energy dispersive spectrum of the ternary NiFeZn alloy coating prepared in Example 1.

[0023] Figure 2 This is the X-ray energy dispersive spectrum of the self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst prepared in Example 1.

[0024] Figure 3 Scanning electron microscope image and element mapping image of the self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst prepared in Example 1.

[0025] Figure 4 This is a transmission electron microscope image of the self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst prepared in Example 1.

[0026] Figure 5 This is the X-ray powder diffraction pattern of the self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst prepared in Example 1.

[0027] Figure 6 The electrochemical performance test data of the self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst prepared in Example 1 in 1M KOH solution is shown in FIG. Figure 6 (a) is the polarization curve diagram of the hydrogen evolution reaction, 6(b) is the stability test diagram of the hydrogen evolution reaction, 6(c) is the polarization curve diagram of the oxygen evolution reaction, 6(d) is the stability test diagram of the oxygen evolution reaction, 6(e) is the polarization curve diagram of the full water decomposition test, and 6(f) is the stability test diagram of the full water decomposition test. DETAILED DESCRIPTION

[0028] Embodiment 1:

[0029] (1) The nickel foam was ultrasonically treated in 3 mol / L hydrochloric acid for 20 min, and then washed with anhydrous ethanol and deionized water and dried;

[0030] (2) In a mixed solution comprising 0.1 mol / L FeSO4, 0.005 mol / L NiSO4, 0.2 mol / L ZnSO4, and 0.4 mol / L Na3C6H5O7 as an electroplating solution, a 10% H2SO4 solution was used to adjust the pH value of the electroplating solution to 5±0.01, nickel foam was used as a working electrode, a Pt sheet was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode, and the NiFeZn alloy coating was obtained by electrodeposition at a voltage of -1.7 V vs. SCE for 1 h, which was then washed with deionized water and anhydrous ethanol and dried;

[0031] (3) The sample obtained in the above step (2) was kept at 450° C. for 10 h under argon atmosphere;

[0032] (4) corroding the sample obtained in the above step (3) in a 1 mol / L NaOH solution at 35° C. for 24 h, and finally obtaining a hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst in situ constructed on the surface of nickel foam;

[0033] (5) The atomic percentage of Ni in the NiFeZn alloy coating obtained after the electrodeposition is 2.90%, the atomic percentage of Fe is 2.87%, and the atomic percentage of Zn is 94.3%. Figure 1 As shown;

[0034] (6) The atomic percentage of Ni in the self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst obtained after the corrosion is 42.15%, the atomic percentage of Fe is 37.75%, and the atomic percentage of Zn is 22.3%. Figure 2 As shown;

[0035] (7) The self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst has a surface layer of a two-stage porous network NiFeZn alloy, a primary pore wall size of about 100nm, a primary pore size of about 400nm, a secondary pore wall size of about 30nm, a secondary pore size of about 6nm, and an alloy layer thickness of about 3.5μm; a base layer of a two-stage porous NiZn-Ni constructed on the surface of nickel foam, a primary pore wall size of about 400nm, a primary pore size of about 700nm, a secondary pore wall size of about 40nm, a secondary pore size of about 10nm, and an alloy layer thickness of 12.5μm, such as Figure 3 and Figure 4 As shown;

[0036] (8) The self-supporting hierarchical porous NiFeZn@NiZn-Ni heterostructure catalyst is composed of NiFeZn alloy, NiZn intermetallic compound and Ni heterojunction, such as Figure 5 shown.

[0037] The electrocatalytic testing scheme of the present invention is:

[0038] Example 1: NiFeZn@NiZn-Ni was prepared as the working electrode, carbon rod as the counter electrode, Hg / HgO electrode as the reference electrode, and 1M KOH solution as the electrolyte solution. The test results are shown in Figure 6 As shown in the figure, the test results show that the hierarchical porous NiFeZn@NiZn-Ni can be used as a HER electrocatalyst at 600 mA cm -2 and 1000mA cm -2 The overpotentials are only 187 mV and 239 mV, and the electrocatalyst can be used as an OER catalyst at 600 mA cm -2 and 1000mA cm -2The overpotentials are only 320 mV and 362 mV, and the bifunctional catalyst can be used in overall water splitting at 600 and 1000 mA cm -2 The cell voltage is only 1.796 and 1.901 V at a current density of , and they both show excellent stability in alkaline electrolyte solutions, which collectively indicates that the catalyst has good commercial application prospects.

[0039] In summary, the present invention provides a method for preparing a self-supporting layered porous nickel-based alloy heterostructure catalyst, which adopts the techniques of electrodeposition, heat treatment and corrosion to prepare a bifunctional catalyst with a layered porous heterostructure and excellent hydrogen evolution and oxygen evolution performance. The catalyst has excellent electrocatalytic activity and low cost, and realizes full utilization of resources and energy.

[0040] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected, and the scope of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst, characterized in that: The nanoporous NiZnM@NiZn-Ni heterostructure catalyst in situ constructed on the surface of nickel foam is prepared by electrodeposition, heat treatment and corrosion technology, wherein M is Fe or Co, the surface layer is NiZnM, and the base layer is a two-level porous NiZn-Ni constructed on the surface of nickel foam, which specifically includes the following steps: (1) immersing the nickel foam in a hydrochloric acid solution for ultrasonic cleaning; (2) using a mixed solution of NiSO4, ZnSO4, M sulfate and Na3C6H5O7 complexing agent as an electroplating solution, using H2SO4 solution to adjust the pH of the electroplating solution, and using a constant potential method in a three-electrode system to electrodeposit an alloy coating with a high zinc content on the surface of nickel foam; (3) annealing the sample obtained in the above step (2) under the protection of argon or nitrogen atmosphere; (4) The sample obtained in the above step (3) is corroded in ammonia, NaOH or KOH solution to obtain a self-supporting hierarchical porous NiZnM@NZn-Ni heterostructure catalyst.

2. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that: In the step (1), the nickel foam is firstly ultrasonically treated in a 1-8 mol / L hydrochloric acid solution for 5-40 min, and then washed with deionized water and anhydrous ethanol and dried.

3. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that: In the mixed solution of step (2), the concentration of NiSO4 is 0.001-0.02 mol / L, the concentration of ZnSO4 is 0.1-0.4 mol / L, the sulfate of M is FeSO4 or CoSO4, and its concentration is 0.01-0.2 mol / L, the concentration of Na3C6H5O7 is 0.25-0.6 mol / L, the mass fraction of H2SO4 solution is 1-40%, and the pH value is 3.0-6.

0.

4. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that: In the step (2), nickel foam is used as the working electrode, the Pt sheet is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The voltage range used is -1.5 to -1.9 V, and the electrodeposition time is 0.5 to 3 hours.

5. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that: In the step (3), the annealing heat treatment temperature is 400-460° C., the heating rate is 2-10° C. / min, and the annealing time is 3-12 h.

6. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that : In the step (4), the concentration of ammonia water, NaOH or KOH solution is 0.2-6 mol / L, the corrosion temperature is 20-50°C, and the corrosion time is 5-60h.

7. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that: (1) The atomic percentage of Ni in the high zinc content alloy coating obtained after the electrodeposition is 2-20%, the atomic percentage of M is 2-20%, and the atomic percentage of Zn is 60-96%; (2) The atomic percentage of Ni in the self-supporting layered porous NiZnM@NiZn-Ni heterostructure catalyst obtained after the corrosion is 20-70%, the atomic percentage of Zn is 15-40%, and the atomic percentage of M is 15-40%.

8. The method for preparing a self-supporting hierarchical porous nickel-based alloy heterostructure catalyst according to claim 1, characterized in that: The self-supporting layered porous NiZnM@NiZn-Ni heterostructure catalyst has a surface layer of a two-level porous network NiZnM alloy, with a primary pore wall and pore size of 100-600nm, a secondary pore wall and pore size of 3-50nm, and an alloy layer thickness of 2-10μm; the base layer is a two-level porous NiZn-Ni constructed on the surface of nickel foam, with a primary pore wall and pore size of 100-900nm, a secondary pore wall and pore size of 3-100nm, and an alloy layer thickness of 5-20μm.